Number-specification in numeral ’cien’: Where generality meets lexical specificity - Camacho, José (Borealis – An International Journal of Hispanic Linguistics, 2025)
Numbers express the primary concept of cardinality, the measure of the number of elements in a set that answers the question how many? Linguistically, they are conveyed through simple (dos ‘two’) or complex (doscientos ‘two hundred’). Although numerals higher than 1 are inherently plural, plurality only overtly appears on cien ‘hundred’ and millón ‘million’ and only when the numeral is part of a multiplicative number (doscientas sillas ‘two hundred.f.pl chairs’ vs. additive ciento dos sillas ‘one and hundred two chairs’). The additive vs. multiplicative constraint on overt number is analyzed as follows: complex numerals have a functional head that encodes plurality. This head is potentially realized as an affix that attaches to the root. Since additive numerals involve coordination, the coordinate structure constraint blocks -s from attaching to the root. Multiplicative numerals, on the other hand, allow for -s to attach to the root, since no additional structure blocks attachment. Plurality only appears overtly on cien ‘hundred’ and millón ‘million’ because the morphological insertion rules for plurality in cardinals treats the null plural as default and the -s plural as marked (and restricted to a few roots). Approximative numerals (miles de personas ‘thousands of people’) obligatorily show plural marking and de, instantiating yet another source of number, a functional DIV(ision) head.